Do European spin-offs really create value? Short-term and long-term perspective - Laukkanen, Anna (My University, 2024)
From the 1960s to the 1980s, numerous companies pursued a strategic approach characterized by conglomeration and diversification within the financial markets of Europe and the United States. This strategic approach led to the emergence of large conglomerate entities as companies acquired other businesses to scale and broaden their sources of revenue. However, conglomerates began facing challenges in managing their diverse portfolios of acquired businesses. A vision emerged, that the separate valuation of the business units could yield a higher worth than the combined conglomerate entity. Consequently, corporate spin-offs became widely recognized as a strategic option for restructuring conglomerates and other corporations to unlock shareholder value. This thesis investigates whether European corporate spin-off transactions result in positive wealth effects for the parent company’s shareholders. The study is motivated by the limited number of previous research done in the European market and the discrepancy in the long-term empirical findings between the U.S. and European capital markets. The analysis is conducted by investigating if the spin-off announcement and the implementation of the transaction generate positive abnormal returns for the parent company’s shareholders. Short-term and long-term event studies are conducted to investigate this matter. Furthermore, the value creation factors are analyzed by using a multivariate least squares regression to attain a deeper understanding of the value creation mechanics of the transaction type. The empirical analysis of this study is based on a data set including 40 corporate spin-off transactions announced in Europe between 2010 and 2020. The findings of this study conclude that European corporate spin-off transactions generate shareholder value, but the positive wealth effects are only restricted around the announcement of the transaction. The results indicate that European spin-off transactions do not demonstrate long-term value creation, unlike the spin-off deals in the U.S. capital market. The created value instantly reflects to the parent company’s share price around the announcement of the transaction as no evidence of abnormal returns is documented in the long-term. Therefore, the findings suggest the market efficiency in the European capital market. Furthermore, the sources explaining the value creation remain unclear. Despite introducing multiple factors potentially contributing to the wealth effects, their statistical significance remains low, failing to explain the value creation of European corporate spin-off transactions.
Keywords: Corporate spin-off, Demerger, Shareholder value, Corporate finance